Relevansi Ajaran Teodisi dan Kesejahteraan Spiritual pada Penyintas Trauma Bencana Alam di Palu - Nole, Otniel Aurelius; Ranimpi, Yulius Yusak; Tampake, Tony (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
The people of Palu experienced natural disasters on September 28, 2018. The event caused suffering in the form of trauma. Society attributes the struggle to the existence of God, as in theodicy. Nevertheless, suffering in human life has spiritual meanings. The purpose of this research was to analyze the relevance of theodicy and spiritual well-being for survivors of natural disaster trauma in Palu. This research used a qualitative method with a phenomenological type. Researchers collected data using interview techniques with five participants who were Palu residents who had experienced natural disasters on 28 September 2018, then analyzed the data through an interpretative phenomenological analysis. Researchers found three categories as themes: natural disasters events, relationships with God, and relationships with others. Researchers showed that all participants realized that natural disasters are devastating phenomena and, in fact, cause trauma. Despite the suffering, they recognized God's goodness, which restores and manifests in empathy and solidarity. Relationships with the divine and others influenced their spiritual well-being.